Comparative diagnostic utility of leptin and resistin as inflammatory biomarkers in acute myocardial infarction - Kadhum, Akram Hassan; Ali, Baida Rihan (European Journal of Clinical and Experimental Medicine, 2025)
Introduction and aim. Acute myocardial infarction (AMI) is a leading cause of mortality. Although traditional risk factors are known, adipokines, such as leptin (LEP) and resistin (RETN), are emerging as potential biomarkers involved in the inflammatory and metabolic processes underlying AMI. This study aimed to evaluate serum LEP and RETN levels in patients with AMI. Material and methods. This case-control study included 60 patients diagnosed with AMI and 60 healthy controls recruited from the Nasiriyah Heart Hospital, Thi-Qar Province. Serum levels of LEP and RETN were measured using an enzyme-linked immunosorbent assay. Results. AMI patients exhibited significantly elevated LEP (3.79±2.0 vs. 1.43±0.7 ng/mL, p<0.001) and RETN (606±325 vs. 289±160 ng/L, p<0.001) compared to controls. Both adipokines were positively correlated with high-sensitive troponin I (Hs-TnI), low-density lipoprotein (LDL-C), and triglycerides (p<0.05). ROC analysis demonstrated a high diagnostic accuracy for LEP (AUC=0.964; cutoff >2.23 ng/mL, derived from internal study data) and moderate accuracy for RETN (AUC=0.878; cutoff >305.9 ng/L). The sensitivity and specificity of the LEP were 93% and 92%, respectively. Conclusion. LEP demonstrated high diagnostic accuracy in our cohort, and its clinical application requires validation in larger prospective studies. The association between RETN and AMI likely reflects inflammatory sequelae rather than predictive utility.